Mirror, mirror on the coast: Exploring body image perception and its nexus with self-esteem, mental well-being among student population at an education hub in South-India - Sanjay Kini B; Raghavendra Huchchannavar; Akhila Doddamani; Manjula A; Yash Alok; Sandesh Kini B; Anusha Bhat N; Athulya Krishnan (PLoS ONE, 2025)
Introduction Young people’s body image dissatisfaction (BID) is a worrying problem that could impact both their physical and mental health. In addition to determining the prevalence and severity of BID among college students in the coastal region of Karnataka, India, this cross-sectional study investigated the relationship between BID and anxiety, depression, and self-esteem. Materials and methods Data was gathered using a variety of social media channels from a sample of 382 students who were older than 18 years. The following validated measures were used: the Hamilton Anxiety Rating Scale for anxiety, the Stunkard Figure Rating Scale for depression, the Body Shape Questionnaire-16B for body shape concern, the Rosenberg Self-Esteem Scale for self-esteem and the Patient Health Questionnaire-9 for depression. Additionally, self-reported anthropometric data and sociodemographic information were gathered. Results According to the study, 73.03% of participants had a negative perception of their bodies and strongly preferred to have a smaller ideal body image. BID showed a positive correlation with anxiety and depression and a negative correlation with self-esteem. When compared to pupils with normal BMI, those who were overweight or obese showed considerably higher probabilities of being unhappy with their body image. A curious discrepancy between body image dissatisfaction and body form concern was noted, indicating the necessity for a multifaceted evaluation. Conclusion The results highlight the significance of providing thorough, evidence-based therapies that are customized to the individual requirements of college students to address body image concerns. Using a comprehensive strategy that incorporates psychological, emotional, and physical health can help students succeed and thrive.